Populism, “Anti” Ideologies, and Feminist Coalitions - Ackerly, Brooke A. (Frontiers in Sociology, 2021)
By understanding anti-democratic populism as an “anti-politics” (directed at groups of people), we can identify within progressive activism a corresponding anti-structural injustice politics. Attending to the potential of this anti-structural injustice activism encourages activists to expand their coalitional politics and government and philanthropic donors to see the import of funding work against structural injustice that explicitly takes on patriarchy and racism, among the full gamut of ideologies based on hierarchy and injustice.